(untitled) (Global Journal of Human-Social Science, 2021)
The Sundarbans, lies on the delta of the Ganges, Brahmaputra and Meghna rivers on the Bay of Bengal, is the largest contiguous mangrove forest in the world. Although the mangrove forests of the Sundarbans provide an important defense in limiting climate change impacts, the forest ecosystems have now become vulnerable due to the effects of climate change. The climate change of the region has been studied through statistical analysis of records of last thirty years of rainfall, temperature, sea level and sea surface temperature. Several statistical techniques such as Mann-Kendall/Modi fied Mann-Kendall tests, Theil and Sen’s median slope analysis, simple linear regression method were applied for the study and data used from observed and gridded datasets. The annual rainfall has been decreased by 6.6% at a rate of 5.25 mm/yr. The atmospheric temperature has shown an increasing trend throughout the year except for the winter season which indicates that winter has become colder and summer has become warmer.